Orthogonal differential eddy current testing for internal detection of oil and gas pipeline based on incremental permeability extraction - Yanshuang GONG; Xiaokang WAN; Hongjun WANG; Jiaxing XIN; Guangming CHEN; Jinzhong CHEN; Bingfeng YU; Yilai MA (You-qi chuyun)
Objective Serving as the primary mode of transporting oil and natural gas, pipelines are prone to corrosion, cracks, and other defects under intricate operational conditions. However, conventional magnetic flux leakage testing equipment faces challenges in navigating small-diameter and low-pressure pipelines due to its bulkiness and strong magnetic field attraction. Additionally, this method falls short in pinpointing minor defects. The traditional eddy current testing technique is constrained by the skin effect, impeding its ability to identify outer wall flaws and buried defects, as well as discerning defect depths accurately. Furthermore, ultrasonic testing proves impractical for natural gas pipelines due to the need for couplants. Methods This paper presents a novel pipeline defect detection technique that combines DC magnetization and orthogonal differential eddy current methods. Initially, the impact of inner and outer surface defects on the internal eddy current field and magnetic permeability of pipelines was investigated using finite element analysis. Following this, an orthogonal differential eddy current testing probe was developed. Subsequently, dynamic scanning experiments were carried out to detect defects on the inner and outer surfaces of pipelines. Results The developed orthogonal differential eddy current testing probe generated signals in response to corrosion on the inner and outer walls as well as cracks in the inner wall. Within a certain range, the peak defect depth and width of the characteristic signal are positively correlated, and the peak and valley spacing are positively correlated with the defect width. The buried defects in pipelines have the same phase as the characteristic signals of the outer wall defects and are opposite to the characteristic signals of the inner wall defects, which can provide a reference for rapid determination of defect locations. Conclusion The research findings present a methodology to address the shortcomings of traditional magnetic flux leakage and eddy current testing techniques, providing a valuable perspective for advancing the technological development of on-line pipeline testing.